The Role of the Family' and School Environments in Instilling Citizenship Values as Perceived by Primary School Teachers in Sirte, Libya (Abhat Journal, 2025)
The study aimed to identify the role of both the family and school environment in inculcating citizenship values among students as perceived by teachers of basic education in Sirte, To achieve this goal, the researchers used the descriptive approach, and a questionnaire was designed as a tool for collecting data from the respondents, represented in the teachers of the second part of the basic education stage in (10) schools distributed in the neighborhoods of the central city of Sirte, and the size of the study population was (238), and the study was conducted on a sample Its size is (147) parameters, and after the statistical analysis of the data, the researchers reached a set of results, the most important of which are: The family environment has a role in instilling the values of citizenship among students with an average of (2.07) at an average level, and the school environment has a role in inculcating the values of citizenship among students with an average of (2.22) at an average level, and that the family seeks to consolidate the values of citizenship among its children, as this paragraph got the highest An arithmetic average in the family environment axis, which is (2.48), which is at the high level. Teachers believe that inculcating the values citizenship among students is one of the goals of the educational process in the first place, with the highest average, which is (3). As for the school curricula, it does not adequately cover its role in inculcating the values of citizenship among students, with a low mean (1.09).
Keywords: family environment; school environment; basic education; citizenship values